2021
DOI: 10.26803/ijlter.20.7.15
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Students’ Challenges on Flexible Online Learning Implementation in the Rural Areas: A Philippine Case

Abstract: The COVID-19 Pandemic has led Higher Education Institutions (HEIs) in the Philippines to replace on-campus learning with flexible learning. This paper explores the students' challenges on flexible online learning implementation of the university in the rural area based on their background and experience. This employed quantitative and qualitative methods through a survey and an interview respectively sought to gather data from 639 university students. Data were analyzed with descriptive statistics and narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 62 publications
1
13
0
2
Order By: Relevance
“…Impliedly, this seriously challenges learning in an online context. In this regard, Gocotano et al (2021) document that because of lack of ICT skills, students in the Philippines struggled to reach their fellow students and participate in learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impliedly, this seriously challenges learning in an online context. In this regard, Gocotano et al (2021) document that because of lack of ICT skills, students in the Philippines struggled to reach their fellow students and participate in learning.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of low-level surrounding the region's science and technology threaten to undermine the effectiveness and efficiency of online learning systems. In this regard, studies from Zimbabwe (Mutatana, 2019) and the Philippines (Gocotano et al, 2021;Rotas & Cahapay, 2020) found that poor access to internet services and unstable electricity supply limit students' access to learning resources in their locations. Problems such as low bandwidth and load shedding, coupled with frequent power cuts, are prevalent in many developing countries.…”
Section: Students' Online Learning Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Readiness was measured by asking respondents question about access to devices and the internet, computer skills, ability to express themselves and communicate with teachers and peers using online tools, and availability of administrative and technical support. Challenges to flexible learning are skewed especially towards students living in rural areas where there is a reported shortage of elearning devices, various distractions in the learning environment, poor internet connection, and loss of motivation (Gocotano et al, 2021).…”
Section: Outcomes Of the Covid-19 Pandemic On Inclusionmentioning
confidence: 99%
“…Most families only own one digital device for learners and often need to share (Hagedorn et al, 2021). Besides that, learners probably have outdated appliances and are only compatible with lower technological software (Gocotano et al, 2021).…”
Section: Lack Of Appropriate Devicesmentioning
confidence: 99%